Электротехническая "война" постоянного и переменного токов: краткая история и области их современного применения - Баранов, Михаил Иванович; Шерстюкова, Татьяна Дмитриевна (НТУ "ХПИ", 2010)
Приведен краткий очерк из всемирной истории становления, противостояния и электротехнического применения постоянного и переменного токов.

A short essay is resulted from world history of becoming, opposition and electrical engineering application of direct and alternative currents.
Electrical engineering "war" of direct and alternative currents: short history and their modern application domains
Keywords: Майкл Фарадей; история электротехники; современная электротехника; переменный ток; постоянный ток; Никола Тесла; Джордж Вестинхауз; система переменного тока; тяговые двигатели; history of electrical engineering; direct and alternative currents; Electrical engineering